Life cycle energy minimization of autonomous buildings. (July 2020) - Grazieschi, Gianluca; Gori, Paola; Lombardi, Lidia; Asdrubali, Francesco
Abstract: This work aims at investigating the existence of an optimal solution from the life cycle energy point of view of an autonomous building. The life cycle energy demand of a building can be divided into three parts: the operational energy, the embodied energy and the end-of-life one. The introduction of renewable energy resources generally causes a shift of the energy demand from the operational phase to the embodied and end-of-life ones. The study aims at demonstrating that, in autonomous buildings, the relationship between total life cycle energy demand and operational energy demand is characterized by an optimal level that minimizes the overall life cycle energy demand of the construction. An autonomous building, representative of the Italian context, was chosen as a case study and, analysing different design configurations, it was observed that the low energy design solution performed better than the net zero energy building from a life cycle energy perspective. Highlights: The life cycle energy optimization of an autonomous building is performed. An optimal solution, that minimizes the overall life cycle energy, exists. Electrical energy storage systems can induce an important burden shifting. The low-energy design performs better than the NZEB solution. Grid connected buildings perform better than autonomous constructions.